Voices of university students during the COVID-19 contingency - Hernández y Hernández, Denise; López González, Rocío; Alarcón Montiel, Esmeralda (Opción, 2022)
The COVID-19 pandemics had a negative impact on undergraduate students, specifically, those coming from low income families. The purpose of this study was to analyze qualitatively which undergraduate courses were chosen by students. We conducted 12 interviews to undergraduates registered at Universidad Veracruzana, Mexico. We found students experienced several inequalities during this period, upon variation in living and housing conditions, family income, lifestyle, gender and state of mind.